Investigating the Applicability of the Peak Density Thickness Parameter over the Equatorial Region - Mohamed O. Shammat; Bodo W. Reinisch; Ivan Galkin; Philip J. Erickson; Jay A. Weitzen; William C. Rideout (Atmosphere)
The Peak Density Thickness (PDT) refers to a vertical region in the ionosphere encompassing the F2 peak, where electron density is at its maximum, and extending upward—maintaining a constant density—for a fixed altitude beyond this peak. This study builds on the previously established PDT concept, initially explored at midlatitudes using data from Millstone Hill, by evaluating its applicability and effectiveness over equatorial latitudes using data from the Jicamarca Incoherent Scatter Radar (ISR) in Lima, Peru. A comprehensive analysis of electron density profiles measured by the Jicamarca ISR, spanning 1997 to 2020, was conducted using the Madrigal database to extract the PDT parameter for the F2 layer. Findings from the Jicamarca ISR indicate that the PDT parameter peaks around solar noon, aligning with observations from Millstone Hill. For selected case studies, the Vary-Chap topside model was employed to reconstruct the ionospheric profile above the F2 peak and PDT, demonstrating the model’s enhanced effectiveness when incorporating the PDT parameter over equatorial regions. This research confirms the presence of PDT in equatorial regions, consistent with its behavior at midlatitudes, and underscores the importance of PDT in refining predictive ionospheric models across different latitudes.